P-selectin gene haplotypes modulate soluble P-selectin concentrations and contribute to the risk of venous thromboembolism - Ay, Cihan; Jungbauer, Lea V.; Kaider, Alexandra; Koder, Silvia; Panzer, Simon; Pabinger, Ingrid; Mannhalter, Christine (Thrombosis and Haemostasis, 2008)
The cell adhesion molecule P-selectin mediates the interaction of activated platelets or endothelial cells with leukocytes. In arterial and venous thromboembolism (VTE) increased soluble P-selectin (sP-selectin) concentrations have been found, and associations of P-selectin genotypes with thrombotic disease have been proposed. We assessed the effect of four single nucleotide polymorphisms (SNPs) [one in the promoter region (c.–2123C>G) and three (S290N, c.1087G>A; D562N, c.1902G>A; T715P, c.2363A>C) in the coding region] and the calculated haplotypes in the P-selectin gene (SELP) on sP-selectin concentrations and VTE risk. The analysis was carried out in 116 high-risk patients with a history of objectively confirmed recurrent VTE and 129 age- and sex-matched healthy individuals. Haplotypes were generated using computer-assisted haplotype reconstruction with Phase 2.1. sP-selectin (μg/l) was measured by ELISA. Frequencies of all four individual SNPs were not statistically significantly different between patients and controls. Tenhaplotypes were obtained for the control population, and nine for the patient group. The most frequent haplotype among controls was CGGA (major allele at all positions) (27.8%; frequency in patients 19.0%), which was used as reference for statistical analyses. Among patients GGAA was most frequent (23.3%; frequency in controls 17.5%). Haplotypes were significantly associated with sP-selectin concentrations in patients and in controls (p<0.001 and p=0.011). Compared to CGGA some but not all haplotypes conferred an increased risk for VTE with odds ratios (ORs) between 5.4 (95% CI: 2.5–12.2) for CAGA, 3.3 (1.2–9.2) for CGAC, and 2.4 (1.3–4.7) for GGAA. All ORs remained statistically significant after adjustment for the factor V Leiden mutation, located in close proximity to SELP on chromosome 1, as well as all other established risk factors for VTE. In conclusion, SELP haplotypes modulate plasma concentrations of sP-selectin and affect the risk of recurrent VTE.
Keywords: P-selectin; haplotypes; deep venous thrombosis; pulmonary embolism; venous thromboembolism